2009
DOI: 10.1177/0956247809344364
|View full text |Cite
|
Sign up to set email alerts
|

The limits of land titling and home ownership

Abstract: This paper reviews whether land titling programmes have achieved the benefits claimed by their proponents. It finds that they have generally failed to do so. Investment in land and housing, access to formal credit, and municipal revenues have not increased noticeably more than under other tenure regimes, including those that allow many unauthorized settlements, and there is no significant evidence of poverty levels being reduced. Titling does provide increased tenure security — but many alternative forms of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
164
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(182 citation statements)
references
References 14 publications
(3 reference statements)
2
164
0
4
Order By: Relevance
“…The provision of formal titles through registration does not solve the problem of land disputes especially in the continent of Africa. As noted by Payne et al (2009) in several areas including India, Mexico, Peru, South Africa, Tanzania, Senegal and Egypt, de facto security already existed before the introduction of land registration programs; indeed in Afghanistan and India for instance, it is reported that registration actually led to a reduction in tenure security. It is probably in this regard that Atwood (1990) argues that land registration could actually reduce security and lead to more conflicts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The provision of formal titles through registration does not solve the problem of land disputes especially in the continent of Africa. As noted by Payne et al (2009) in several areas including India, Mexico, Peru, South Africa, Tanzania, Senegal and Egypt, de facto security already existed before the introduction of land registration programs; indeed in Afghanistan and India for instance, it is reported that registration actually led to a reduction in tenure security. It is probably in this regard that Atwood (1990) argues that land registration could actually reduce security and lead to more conflicts.…”
mentioning
confidence: 99%
“…They argue that titling enhances tenure security, helps to secure investments; supports land markets to evolve more efficiently; improves access to formal credit and helps to reduce poverty and ultimately expedites economic development (Payne et al, 2009;UNECE, 2005;World Bank, 2006). The economic impact of formal property titles is derived from the assurance effect -certainty that 4 property owners will be able to reap the fruits of their investment and the collateralisation effect -the ability of property owners to use their properties as collateral for credit (Brasselle et al, 2001;de Soto, 2000).…”
mentioning
confidence: 99%
“…Despite some evidence of shifts towards flexible tenure arrangements, emphasis is still mostly placed on ownership based on individual (or joint) property titles; however the success of titling programmes is heavily context-dependent. There is increasing evidence that titling is both difficult to implement in many urban situations and does not deliver all the benefits claimed for it (Payne et al, 2009;Rakodi, 2016). This consideration underlines a third analytical challenge relating to the potential for tenure formalisation or legalisation to create as well as ameliorate conflict, as discussed in Lombard's, Rigon's and Patel's papers (Lombard, 2016;Patel, 2016;Rigon, 2016).…”
Section: Towards An Analytical Frameworkmentioning
confidence: 99%
“…Payne et al, 2009;Rakodi, 2014Rakodi, , 2016 to situations characterised by conflict and violence related to land, in particular identifying the nature and effects of dissonance between different land regimes and assessing whether land policy and interventions have ameliorated, exacerbated or even caused conflict over land. This issue is highlighted by Van Leeuwen and Van der Haar (2016), and emphasised in several of the papers, which compare a given policy's intended outcomes with its effects in reality.…”
Section: Conclusion: Key Challenges For Research and Policymentioning
confidence: 99%
“…If, with the translation in English of The Other Path, the success of de Soto reached an international level, in 2000, with the publication of The Mystery of Capital, he reached a level of popularity that allowed him to win several prizes, get a Nobel Prize nomination, and gain the support of politicians, policy makers, and international organizations all over the world (Gilbert, 2002;Bromley, 2004;Gravois, 2005;Sjaastad & Cousins, 2008;Otto, 2009;Payne, Durand-Lasserve and Rakodi, 2009;Obeng-Odoom, 2013). The publication of The Mystery of Capital stimulated a significant wave of recognitions, appreciations, and a relevant media echo.…”
Section: Consensusmentioning
confidence: 99%